The The Influence of Self-Efficacy, Motivation, and Information Technology on Teacher Performance at Junior High Schools in North Balikpapan - Fauziyyah; Azainil Azainil; Widyatmike Gede Mulawarman (PT ARRUS Intelektual Indonesia, 2024)
Self-efficacy, motivation and information technology can be supporting factors in achieving optimal teacher performance because high self-confidence and enthusiasm, as well as good self-development will increase teacher professionalism in order to achieve quality education. This research aims to find out whether self-efficacy, motivation and information technology have an influence on the performance of State Middle School teachers in North Balikpapan. The sample of 152 teachers was obtained. Then the researcher used a random sampling technique to determine the respondents in this study. The data analysis technique used is multiple linear regression, which is processed using the SPSS program. From the results of research and data analysis carried out by researchers using the t test, it was found that self-efficacy, Motivation, and Information Technology partially had a significant effect on the performance of State Middle School teachers in North Balikpapan. Then, simultaneously through the F test, it was found that self-efficacy, motivation and information technology had a significant effect on the performance of State Middle School teachers in North Balikpapan. This shows that if there is an increase in self-efficacy, motivation and information technology, it will improve the performance of State Middle School teachers in North Balikpapan.